Resilient Supply Chains: Strategies for Managing Disruptions in a Globalized Economy - Karanam, Raghunath Kashyap; Sachani, Dipakkumar Kanubhai; Natakam, Vineel Mouli; Yarlagadda, Vamsi Krishna; Kothapalli, Kanaka Rakesh Varma (American Journal of Trade and Policy, 2025)
This paper investigates methods for creating robust supply chains in a worldwide economy in light of growing disruptions. The primary goals were to evaluate supply chain resilience through integrating sustainable practices, investigate the impact of new technology, and explore solutions for diversification. A thorough analysis of case studies and literature regarding methodology was carried out, emphasizing secondary data sources from government publications, business reports, and scholarly journals. Significant research indicates that diversifying suppliers, production sites, and logistical routes can reduce the risks associated with localized interruptions. Proactive risk management requires enhanced visibility, predictive analytics, and operational efficiency, which may be achieved by integrating technologies like AI, IoT, blockchain, and cloud computing. Furthermore, integrating sustainability through ethical, sustainable sourcing, and resource-efficient methods reduces environmental and societal dangers and improves brand reputation and economic viability. The policy implications emphasize the need for frameworks that foster technology innovation, sustainability, and stakeholder collaboration. By implementing these tactics and resolving related issues, companies can construct flexible supply networks to sustain operations and competitiveness amidst fluctuations in the worldwide market.